StudData - Database for Studies of Recruitment and Qualification in the Professions, Panel 2 - Terum, Lars Inge (Norwegian Social Science Data Services, 2009)
StudData is a database which will give the grounds for panel and life cycle studies. It is a big and long-term project that include twenty professions. StudData is a collaborative project where eleven university colleges and universities participate. The Centre for the Study of Professions (SPS), Oslo University College (OUC) leads and coordinates the building of the database, which is financed by the Research Council of Norway and Oslo University College. Professor Lars Inge Terum, professor Jens-Christian Smeby and associate professor Håvard Helland have the the professional and administrative responsibility for StudData at SPS. StudData follows individuals from the they begin studying until they are well established in the labour market. This type of panel and life cycle data provide knowledge about the life cycle of the single person, but changes within a single profession/occupation as well as comparison of different professions are interesting aspects. There are three panels (groups) who are followed: StudData-1, students who commenced their education in autumn 2000. StudData-2, students who completed their education in spring 2001 and StudData -3, students who commenced their education in autumn 2004. Phase 1: The beginning of the education - to obtain knowledge about recruiting and motivation to commence studies in a given profession. (Phase 1 only takes place for panel 1 and 3) Phase 2: When the education is completed: to obtain knowledge about views on the content of the education, the way the study was organised, well-being, the formation of a profession identity and the students' thoughts about future work. Phase 3 and 4: Two questionnaires within 5-6 years to obtain knowledge about newly educated persons' encounter with work and occupational life, carreer patterns, resignations from the occupation, cooperation, reflections about education and personal competences. In phase 1 - 2 the data collection is carried out through/in cooperation with the educations/institutions. In phase 3 and 4 the questionnaire is distributed to the respondents by mail. University colleces and universities with educations which are included in StudData: Bergen University College Bodø University College Lillehammer University College Oslo University College Sør-Trøndelag University College Telemark University College Volda University College Aalesund University College University of Bergen University of Oslo University of Stavanger Professions included in StudData: - nurses, physiotherapists, occupational therapists and radiographists. - general teachers, pre-school teachers and specialist teachers in arts and crafts. - social workers, child welfare officers, social educators. - computer engineers, constructions engineers, bioengineers, mechanical engineers, electrical and electronic engineering, applied chemistry. - other educations: medicine, jouralism, accountancy, economic and administrative subjects, library and informastion workers. For acces to the data, please contact Centre for the Study of Professions, Oslo University College http://www.hio.no/content/view/full/9162